The Effect of Metro Expansions on Air Pollution in Delhi - Goel, Deepti; Gupta, Sonam (Published by Oxford University Press on behalf of the World Bank, 2018)
The Delhi Metro (DM) is a mass rapid transit system serving the National Capital Region of India. It is also the world's first rail project to earn carbon credits under the Clean Development Mechanism of the United Nations for reductions in CO2 emissions. We analyze whether the DM led to localized reduction in three transportation source pollutants. Looking at the period 2004–2006, one of the larger rail extensions of the DM led to a 34 percent reduction in localized CO at a major traffic intersection in the city. Results for NO2 are also suggestive of a decline, while those for PM2.5 are inconclusive due to missing data. These impacts of pollutant reductions are for the short run. A complete accounting of all long run costs and benefits should be done before building capital intensive metro rail projects.